Pengembangan Objek 3D Holobox Berbasis Smartphone pada Mata Pelajaran Geografi Kelas X SMA - Alora, Jean Vicky; Rahmi, Ulfia; Zen, Zelhendri; Amilia, Winanda (Lembaga Yasin AlSys, 2023)
The problem with teaching material development study is that of geography learning, suggesting that the materials and media used are not optimal for learning. The teaching materials used use only texts and use oral methods, but the media used her PPT, but the PPT media does not achieve the learning objectives. The use of PPT media has drawbacks in the form of lack of study assignments, students are easily bored and do not study seriously. A lack of learning assignments leads to a lack of enthusiasm in these students, resulting in better student learning outcomes. adversely affected. Study aims to (1) describe the process of developing 3D holograms, (2) generate effective 3D holograms, (3) generate practical 3D holograms, and (4) generate effective learning outcomes. is intended for The type of research (R&D) used in the 4D (Four-D) model. Survey tools in the form of questionnaires and questions. used were in the form of validation media sheets, material validation sheets, and student response questionnaires, using pretests and posttests by subjects in Class X SMA Adabiah 2 Padang. The results of this study show a media validation result of 4.9 (98%) on a very valid basis. The material validation result was 4.6 (94% on very valid criteria). The student's assessment score was 4.41 (88%). Validity results showed a t-count of 7.66 with a t-table of 2.060, so the t-count result > t-table. This means that there is a significant difference in learning outcomes before and after using 3D holographic media. The suitability of 3D holograms as a learning medium for geography .